A modular solution for quick, efficient and secure EU border security.
Border security has become a major political talking-point in Europe over recent years but many argue that more stringent border checks should not lead to a subsequent compromise in speed and efficiency for travellers. In order to strike the right balance, the recently-ended EU-funded FASTPASS project stepped up to offer a next-generation automated border control gate solution.